ESTABLISHMENT OF THE ONE HOUSE ONE Jumantik PROGRAM IN ORDER TO CONTROL DENGUE FEVER (DBD) - Supriyana Supriyana; Betty Saptiwi; Hermien Rimbyastuti; Warijan Warijan (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2016)
Control of DHF with the establishent of the program